Results of the State varietal examination of grain quality for Spring Soft Wheat varieties (Triticum aestivum L.) listed in the State Register of Varieties of Ukraine - О. О. Шовгун; В. В. Шелепов; В. М. Лисікова; С. О. Ляшенко; С. Л. Чухлєб; О. О. Бадяка (Plant Varieties Studying and Protection)
Quality of Spring Soft Wheat varieties listed in the State Register of Varieties of Ukraine for 2008, according to the grain quality indices (protein content, flour vigor, bread volume). Over 86% of Winter Wheat varieties bred by Ukrainian breeders are classified according to their quality to the strong and valuable, in contrast to 14 % of foreign varieties. This is the evidence of the Ukrainian breeding varieties ability to compete.